597. THE ROLE OF SURGERY IN THE ESOPHAGEAL INVOLVEMENT IN SYSTEMIC SCLEROSIS: A SYSTEMATIC LITTERATURE REVIEW. (24th September 2022) - Cerinic, Pietro Matucci; Akpabio, Akpabio; Hughes, Michael; Schoones, Jan; Terrosu, Giovanni; Martino, Antonio; Vecchiato, Massimo; Petri, Roberto; Cerinic, Marco Matucci; Alunno, Alessia
Abstract: In Systemic Sclerosis (SSc), gastroesophageal reflux disease (GERD) occurs in 75% of patients. Chronic doses of proton pump inhibitors may elicit in the general population long-term risk. When medical therapy fails, surgery can be employed but consensus on surgical procedures for refractory GERD is still lacking in SSc. Our aim was to evaluate the surgical approaches employed in the management of refractory GERD with a systematic literature research (SLR). Four research questions, based on the PICO framework, guided the SLR which was conducted up to December 22nd, 2021. The search was performed across different databases including PubMed, MEDLINE (OVID), EMBASE, Cochrane Library, Web of Science, Google Scholar, Emcare and Academic Search Premier. References were independently screened by two reviewers (PMC and AA) who also independently assessed the full text of eligible articles, and extracted data. Due to heterogeneity of retrieved studies, narrative summaries are used to present the data. In 30/916 papers, eligible for review, 348 patients were identified: 257 underwent an anti-reflux surgical procedure and included in the analysis. Refractory GERD was the most frequent indication for surgery, and post-operative dysphagia was a frequent complication. In 18 studies, fundoplication (FP) was effective, whereas 4 studies had equivocal findings and 5 didn't report efficacy. Surgical procedures have changed in time: overall, the Collis-Nissen FP was the most popular in old studies, followed by Nissen FP, while Dor FP has been used more recently. The data extracted show also an acceptable rate of mortality and morbidity related to surgery. In SSc, FP seems a safe and effective procedure for GERD management. In many studies, transient post-operative dysphagia was related with the posterior FP. Our SLR shows that the surgical management of GERD is still highly challenging and minimal requirements should be provided to perform surgical studies in SSc, designing studies to define clinical criteria for surgical referral. In SSc, the right timing for surgery and the best surgical procedure still remain an unmet need.